IMPLEMENTATION OF THE TUMBAS APPLICATION AS A DIGITAL ECOSYSTEM IN PROMOTING THE GROWTH OF MSMES IN MOJOKERTO REGENCY - Yuda, Satya Arya; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the Tumbas application as a digital-based public service innovation initiated by the Mojokerto Regency Government to support the empowerment of local MSME actors, emphasizing not only the provision of technology but also the effectiveness of policy execution and community acceptance. Method: The research adopts a descriptive qualitative approach with data collected through in-depth interviews with policy implementers and MSME actors, field observations, and document analysis. Data were analyzed using the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. Results: The findings show that the Tumbas application has successfully connected MSME actors with the digital market, enhancing accessibility and openness, though challenges persist in technological literacy, sustainability of assistance, and inter-agency coordination. Additionally, bureaucratic structures and human resources have been streamlined to better support this digital service system. Novelty: This research provides an evaluative perspective on the Tumbas application as a localized digital ecosystem, positioning it not only as a transaction platform but also as an instrument of regional economic development policy, integrated with George C. Edwards III’s public policy implementation framework.